Luteolin-stabilized pickering emulsion for encapsulating Enterococcus hirae: preparation, characterization, and synergistic effects on hyperuricemia - Chengtao Han; Songhao Che; Hui-Min Li; Yan-Yu Chi; Jun-Yan Xiang; Qiuhong Xie; Hongyu Xiang (Food Research International, 2026)

The adsorption and fixation of Cd and Pb by the microbial consortium weakened the toxic effect of heavy metal-contaminated soil on rice - Songhao Che; Jianing Wang; Yuanqin Zhou; Chengcai Yue; Xueying Zhou; Yufeng Xu; Shiqi Tian; Zhenning Cao; Xiaoshuang Wei; Siyuan Li; Xue Yang; Zhihai Wu; et al. (Chemical Engineering Journal, 2024)

Boosting freshwater fish conservation with high‐resolution distribution mapping across a large territory - Juan Tao; Chengzhi Ding; Jinnan Chen; Liuyong Ding; Sébastien Brosse; Jani Heino; Virgilio Hermoso; Ruidong Wu; Ziwang Wang; Jiaxin Hu; Rongxiao Che; Xiaowei Jin; et al. (Conservation Biology, 2023)
The lack of high‐resolution distribution maps for freshwater species across large extents fundamentally challenges biodiversity conservation worldwide. We devised a simple framework to delineate the distributions of freshwater fishes in a high‐resolution drainage map based on stacked species distribution models and expert information. We applied this framework to the entire Chinese freshwater fish fauna (>1600 species) to examine high‐resolution biodiversity patterns and reveal potential conflicts between freshwater biodiversity and anthropogenic disturbances. The correlations between spatial patterns of biodiversity facets (species richness, endemicity, and phylogenetic diversity) were all significant ( r = 0.43–0.98, p